Radiative effect of springtime biomass-burning aerosols over northern indochina during 7-SEAS/BASELInE 2013 campaign - Pani S. (2017)
© Taiwan Association for Aerosol Research. The direct aerosol radiative effects of biomass-burning (BB) aerosols over northern Indochina were estimated by using aerosol properties (physical, chemical, and optical) along with the vertical profile measurements from ground-based measurements with integration of an optical and a radiative transfer model during the Seven South East Asian Studies/ Biomass-Burning Aerosols & Stratocumulus Environment: Lifecycles & Interactions Experiment (7-SEAS/BASELInE) conducted in spring 2013. Cluster analysis of backward trajectories showed the air masses arriving at mountainous background site (Doi Ang Khang; 19.93°N, 99.05°E, 1536 m above mean sea level) in northern Indochina, mainly from near-source inland BB activities and being confined in the planetary boundary layer. The PM 10 and black carbon (BC) mass were 87 ± 28 and 7 ± 2 μg m –3 , respectively. The aerosol optical depth (AOD 500 ) was found to be 0.26–1.13 (0.71 ± 0.24). Finer (fine mode fraction ≈0.95, angstrom-exponent at 440–870 nm ≈1.77) and significantly absorbing aerosols (singlescattering albedo ≈0.89, asymmetry-parameter ≈0.67, and absorption AOD ≈0.1 at 440 nm) dominated over this region. BB aerosols (water soluble and BC) were the main contributor to the aerosol radiative forcing (ARF), while others (water insoluble, sea salt and mineral dust) were negligible mainly due to their low extinction efficiency. BC contributed only 6% to the surface aerosol mass but its contribution to AOD was 12% (2 times higher). The overall mean ARF was –8.0 and –31.4 W m –2 at top-of-atmosphere (TOA) and at the surface (SFC), respectively. Likely, ARF due to BC was +10.7 and –18.1 W m –2 at TOA and SFC, respectively. BC imposed the heating rate of +1.4 K d –1 within the atmosphere and highlighting its pivotal role in modifying the radiation budget. We propose that to upgrade our knowledge on BB aerosol radiative effects in BB source region, the long-term and extensive field measurements are needed.